Pengaruh Kualitas Pelayanan dan Fasilitas Lahan Parkir terhadap Kepuasan Civitas Kampus - Asep Erik Nugraha; Kusnadi Kusnadi; Sarah Dampang (JIEMS (Journal of Industrial Engineering and Management Systems), 2019)
The demand for accessible parking services and facilities are growing in the University of Singaperbangsa Karawang (Unsika). This occurred due to the increasing number of vehicles need parking spaces. Some problems can happen because of scrambling over the space, the improper of parking lot building, the ineffective actions in allocating and checking the traffic signs, and the unavailability of traffic signs. The focus of this research was the campus community who use the parking lot. They became the object of the research. The data analysis was used to determine the level of the satisfaction of the campus community towards the service quality and parking facilities in Unsika using the Wilcoxon Signed Rank Test method with Statistical Product and Service Solutions (SPSS) application. The results showed that the campus community was complaining about the quality of service and parking facilities. The perceptions were given in the form of negative perceptions because it was not in line with expectations. The respondents were hoping that the university would pay attention to the quality of services and facilities.